Tanggung jawab hukum konten promosi digital dalam perspektif hukum ekonomi syariah - Wijaya, Alfan Nasrulloh (Maliki Interdisciplinary Journal, 2026)
The utilization of digital promotional content across online platforms has dramatically increased due to the advancements in social media and information technology. Endorsements and paid commercials are two common forms of digital promotion used to sway customers, especially Generation Z. In actuality, though, a lot of advertising materials include inflated, deceptive, and opaque facts, which can result in legal problems and harm to consumers. The purpose of this study is to investigate legal liability for digital promotional information from the standpoint of Islamic economic law. The study uses statutory, conceptual, and maqāṣid al-sharī‘ah methodologies as part of a normative legal method. Qualitative descriptive analysis was used to examine the information gathered from primary, secondary, and tertiary legal sources. The results show that digital platforms, influencers, and corporate actors are legally liable for the promotional content they distribute. From the standpoint of Islamic Economic Law, digital marketing must adhere to the values of justice, honesty, and transparency while avoiding aspects of dishonesty and gharar. In addition to having legal repercussions, breaking these rules runs counter to maqāṣid al-sharī‘ah's goals of preserving wealth and guaranteeing economic justice.